2018
DOI: 10.1002/chem.201706080
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Selective C−C Coupling of Allylic Alcohols with Free Indoles: Influence of the Metal Catalyst

Abstract: Versatile reactive activities of allyl alcohols with free indoles in C-H functionalization reactions were investigated. Direct alkylation or cascade cyclization reactions could be selectively controlled based on the catalyst system: Ru(PPh ) Cl provided C3-substituted β-ketone indoles whereas [Ru(p-cymene)Cl ] yielded cyclized indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Besides indoles, a broad scope of substances, such as pyrroles and other azoles, are exhibited with further applications leading to 3,4-fused tricyclic indoles. Dong [57] also reported direct alkylation or cascade cyclization reactions on C3 of indoles (Scheme 32). With the Ru(PPh3)3Cl2 catalyst, the reaction provides C3-substituted β-ketone indoles and [Ru(p-cymene)Cl2]2 affords 5,12-dihydrobenzo [6,7] cyclohepta [1,2-b] indoles.…”
Section: Scheme 26mentioning
confidence: 99%
“…Besides indoles, a broad scope of substances, such as pyrroles and other azoles, are exhibited with further applications leading to 3,4-fused tricyclic indoles. Dong [57] also reported direct alkylation or cascade cyclization reactions on C3 of indoles (Scheme 32). With the Ru(PPh3)3Cl2 catalyst, the reaction provides C3-substituted β-ketone indoles and [Ru(p-cymene)Cl2]2 affords 5,12-dihydrobenzo [6,7] cyclohepta [1,2-b] indoles.…”
Section: Scheme 26mentioning
confidence: 99%
“…Deuterium was observed at both ortho -positions of phenyl ring (68%) and C3 position of indole ring (74%) when the reaction was carried out in the absence of 2 using DCE/CD 3 OD as the solvent (Scheme c). The H/D exchange of ortho -positions of the phenyl ring indicated that the reaction underwent coordination of nitrogen, and the H/D exchange of the indole ring may be due to the strong nucleophilic property of C3-position which easily attacks rhodium cation followed by metal protonation . Another control experiment showed that no deuterium exchange at the ortho -positions of the phenyl ring was seen in the absence of a rhodium catalyst (Scheme d), suggesting that the rhodium catalyst is essential for this reaction.…”
mentioning
confidence: 99%
“…In 2017, Dong et al reported a Ru-catalyzed cascade C–H allylation and oxidative annulation of 2-phenylindoles with allyl carbonates (Scheme a) . Subsequently, they studied Ru-catalyzed cascade cyclization reactions of 2-phenylindoles with allyl alcohols (Scheme b) . Inspired by these pioneering studies and to broaden the scope of nitrogen heterocycles readily accessible via C–H activation/annulation of 2-arylindoles, we envisioned the use of 2-arylindoles as building blocks for the synthesis of indolo­[2,1- a ]­benzazepinones via a cascade reaction involving C–H activation/intramolecular annulation in the presence of various allyl alcohols (Scheme c).…”
mentioning
confidence: 99%
See 2 more Smart Citations